How patrons value casino promotional offers: A conjoint study. Issue 4 (June 2020) - Legg, Mark; Hancer, Murat
Casinos rely extensively on free slot play (FSP) offers for incentivizing patron visitation. However, there has been a lack of understanding its influence on driving patron visitation and patrons' valuation of FSP compared to other casino promotional offers. This study conducted a conjoint analysis on patrons' valuations of FSP compared to other promotional offerings at a casino resort. Moreover, this study investigated the roles inter-casino competition and visitation frequency have on patrons' perceived valuation of FSP through a hierarchical Bayes model. The results show that competition plays a significant negative role on patrons' valuation of FSP, while competition held insignificant influence on patrons' valuation of food and beverage (F&B) comp offers. Additionally, patrons who visited the casino more frequently valued FSP greater, while less active patrons valued F&B comp offers more. Using the study's results, casinos can increase their margins through increased efficiencies with their promotional offering mix.